STRATEGI PENGEMBANGAN ESPACE SPA BALI DALAM MENGHADAPI PERSAINGAN GLOBAL - Isa Wahjoedi Dwi Poetranto; Lukia Zuraida (Institut Pariwisata dan Bisnis Internasional, 2018)
This research aim to find out the development strategies of Espace Spa Bali in facing global competition, to find out the the guests characteristic and to find out of the guest push and pull motivation in visiting Espace Spa Bali. Random sampling was used with total sample of 45 guests (15% of 300 visiting guests in a month). The data were taken from interview and questionnaire. The SWOT analysis technique was used to analyze the data obtained through the interview, and the descriptive frequency technique was used to analyze the guests characteristics and motivation questionnare data. The result of research showing that Espace Spa Bali is on quadran I (aggressive) with x axis (2.50) and y axix (2.45). the developed strategies are strengthening the brand, quality, marketing and price, also increasing the cooperation with stakeholders. The guest mostly female coming from Australia, France and Japan with the education background from senior high school, diploma, bachelor degrees, ages range from 26 till 56 years old, married status and single are balanced. Guests mostly has job as a staff or office employees and first time visiting Bali. The push motivation factor are indicate that the reason guests visiting Espace Spa Bali for rejuvenation, social an joy, luxury life style, health and beauty, relaxation, escape from routin job. The pull motivation factor are indicate that the guests choose Espace Spa Bali because of proffesionalism and attitude of therapist, good amenities, clean and tidy facility, the room decoration adjust for comfortable treatment Keywords: Global Competition, Development Strategies, Characterics, Push Motivation, Pull Motivation